Re-inventing educational leadership for school and community transformation: learning from the Educational Leadership Management and Development programme of the University of Fort Hare - Moyo, George (Rhodes University, Faculty of Education, Department of Education, 2005)
This study explores educational leadership development and social change strategies pioneered by one programme, the Educational Leadership Management and Development (ELMD) programme of the University of Fort Hare. The programme seeks to model a way of doing social and educational transformation through educational leadership development. Conceptually, the model was meant to draw together a number of education stakeholders operating at various levels of the schooling system to undergo the same programme of leadership development. The programme participants, who included district education officials, schools principals, members of school management teams, educators and members of School Governing Bodies, were to enrol as teams. They would work on learning tasks that were both academic and practical in nature, with an emphasis on experiential learning that leads to the creation of district and community networks of partners, development teams or forums and communities of practice, as well as the production and implementation of district and school development plans. Informed by this conceptual position, the study was structured by two underlying questions. First, whether the ELMD was re-inventing educational leadership beyond the traditional focus on principalship towards one that is inclusive of other education stakeholders. Second, how leadership development as a vehicle for social and educational change can be carried out. The research process was guided by a multi-paradigm perspective which drew heavily on the interpretive and critical science orientations. This led to the crafting of research methods that looked for data that would assist in an understanding of what was happening in the programme, as well as what power dynamics were at play and with what consequences for innovation. The evidence emanating from the study suggests a number of possibilities for consideration by future leadership development programme designers. First, the ELMD programme delivery design shows what can be done to draw participants from various levels of the schooling system, district, school and community and teach them educational leadership together in a mode that mobilizes them for change. Second, how social distance separating different levels of the education hierarchy and status consciousness may disappear gradually as people are brought together to work on tasks of mutual concern. Third, after a year of engagement with ELMD ideas and approach, the participants in the programme appeared to have started a journey of selftransformation towards becoming qualitatively different people who saw themselves as teams capable of tackling education and social problems in their schools and communities. These participants had begun to forge working networks, but the extent to which these could be characterized as knowledge ecosystems and communities of practice remains a question to explore. Fourth, that the current higher education accreditation policies and practices do not accommodate innovative learning approaches of the kind that the ELMD is developing. In this regard, the ELMD experienced difficulties in coming up with an assessment policy and practices which meet the academic as well as the practical developmental concerns of the programme. Fifth, programme instrumentalities and mandates that are put in place do not, in themselves, bring about change. The actual change comes about through the actions of human leadership capable of navigating between structural enablers and constraints.
Keywords: University of Fort Hare; Educational Leadership; Management and Development; Educational leadership -- South Africa; Educational change -- South Africa; School management and organization -- South Africa; School improvement programs -- South Africa; School principals -- South Africa; Community and school -- South Africa